1987
DOI: 10.1017/s0950268800062142
|View full text |Cite
|
Sign up to set email alerts
|

Does chloramphenicol remain the drug of choice for typhoid?

Abstract: SUMMARYOf 2356 strains of Salmonella typhi isolated in Britain in the 8-year period 1978-85,2345 (99 53 %) were sensitive to all antibiotics tested and 11 (0 47 %) were chloramphenicol-resistant; chloramphenicol resistance was plasmid-mediated in 6 strains. It is concluded that chloramphenicol remains a satisfactory first-line choice of drug for typhoid fever in Britain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1988
1988
2010
2010

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…On the basis of these findings, in 1987 it was recommended that in the United Kingdom chloramphenicol should remain the first-line drug for treatment of typhoid fever and, in particular, that it should be used until the results of laboratory susceptibility tests are known [25]. In the succeeding 4-year period (1986-1989), the isolation of chloramphenicol-resistant S. typhi from patients in the United Kingdom increased slightly, from 0.25% to 1.5% [26], but the increase was not considered sufficient to justify altering the recommendation made in 1987.…”
Section: Drug Resistance In British Isolatesmentioning
confidence: 99%
“…On the basis of these findings, in 1987 it was recommended that in the United Kingdom chloramphenicol should remain the first-line drug for treatment of typhoid fever and, in particular, that it should be used until the results of laboratory susceptibility tests are known [25]. In the succeeding 4-year period (1986-1989), the isolation of chloramphenicol-resistant S. typhi from patients in the United Kingdom increased slightly, from 0.25% to 1.5% [26], but the increase was not considered sufficient to justify altering the recommendation made in 1987.…”
Section: Drug Resistance In British Isolatesmentioning
confidence: 99%
“…Until a few years ago, drug-resistant Sal. typhi were uncommon in the UK and USA [11], Rowe et al [12] found drug resistance in only 11 (0.47%) of the 2,356 strains of Sal. typhi iso lated in the UK during 1978-1985, with clini cally significant resistance to chlorampheni col in only 6 strains.…”
Section: Resultsmentioning
confidence: 99%
“…Until 5 years ago, drug-resistant S. typhi were uncommon in the UK and USA [11], Rowe et al [12] studied 2,356 strains of S. typhi isolated in the UK during 1978-1985 and found drug resistance in only 11 (0.47%) strains, with only 6 strains showing clinically significant resistance to chloramphenicol. However, recently drug resistance, especially in developing countries, has become a major problem.…”
Section: Discussionmentioning
confidence: 99%